Kaidah Hukum Yurisprudensi Dalam Peradilan Tata Usaha Negara Dan Kaitannya Dengan Good Governance (Analisa Kasus Putusan Mahkamah Agung Nomor Register : 489 K/TUN/2001) - Ngimadudin Ngimadudin (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2016)
Law basically has the goal of harmony, community dynamics developed so quickly require the progressive concepts that provide guidance to the direction of harmonization kehidupannitu own. What was decided by the Supreme Court in the case of licensing is already running the proportion was expected to justice society, when the dissatisfaction of the government giving an arbitrary policy. On the other hand to lead to the creation of good governance is not an easy matter. Nickname country envelope